Indocyanine green fluorescence lymphography during gastrectomy after initial endoscopic submucosal dissection for early gastric cancer. Issue 6 (7th February 2020) - Roh, C. K.; Choi, S.; Seo, W. J.; Cho, M.; Son, T.; Kim, H.‐I.; Hyung, W. J.
Abstract : Background: Indocyanine green (ICG) fluorescence lymphography can be used to visualize the lymphatic drainage of gastric cancer. Few studies have been performed to identify lymphatic drainage patterns after endoscopic submucosal dissection (ESD). ESD results in changes to lymphatics owing to fibrosis of the submucosal layer. This study aimed to evaluate the efficacy of ICG fluorescence lymphography for visualization of lymphatic drainage after ESD, and to assess its clinical application in additional gastrectomy after ESD for early gastric cancer. Methods: All patients who underwent gastrectomy after ESD between 2014 and 2017 in a single centre were reviewed. ICG was injected endoscopically into the submucosal layer around the ESD scar the day before surgery. At the time of surgery, lymph nodes (LNs) were visualized and lymphadenectomy was performed with near‐infrared imaging. Ex vivo, all LNs were examined for the presence of fluorescence. Number of LNs resected and number of tumour‐positive LNs were compared between patients who underwent near‐infrared imaging and those who had conventional lymphadenectomy without intraoperative imaging. Results: Some 290 patients underwent gastrectomy after ESD, 98 with fluorescence lymphography‐guided lymphadenectomy and 192 with conventional lymphadenectomy. Fluorescence lymphography visualized lymphatic drainage in all patients, without complications related to ICG injection or near‐infrared imaging. Fluorescence lymphography visualized all stations containing metastatic LNs. The sensitivity for detecting LN metastasis in fluorescent stations was 100 per cent (9 of 9 stations), and the negative predictive value was 100 per cent (209 of 209). One patient with LN metastasis had one non‐fluorescent metastatic LN within a fluorescent station. Conclusion: Fluorescence lymphography successfully visualized all draining LNs after ESD, with high sensitivity and negative predictive value for detecting LN metastasis. Fluorescence lymphography‐guided lymphadenectomy could be an alternative to systematic lymphadenectomy during additional surgery after ESD. Abstract : Indocyanine green fluorescence lymphography clearly visualized draining lymphatics during additional surgery after removal of the primary lesion by endoscopic submucosal dissection. Moreover, it visualized all stations containing lymph node metastasis. Fluorescence lymphography‐guided lymphadenectomy may be a potential alternative to systematic lymphadenectomy for additional surgery. Bright future? Abstract : Antecedentes: La linfografía de fluorescencia con verde de indocianina ( indocyanine green, ICG) visualiza el drenaje linfático del cáncer gástrico. Se han realizado pocos estudios para identificar los patrones de drenaje linfático tras una disección submucosa endoscópica ( endoscopic submucosal dissection, ESD). La ESD introduce cambios de los linfáticos debido a la fibrosis de la capa submucosa. El objetivo de este estudio era valorar la eficacia de la linfografía con ICG para visualizar el drenaje linfático tras ESD y evaluar su aplicación clínica en la gastrectomía adicional después de ESD por carcinoma precoz gástrico ( early gastric cancer, EGC). Métodos: Se revisaron todos los pacientes sometidos a gastrectomía tras ESD entre 2014 y 2017 en un único centro. El ICG se inyectó por vía endoscópica en la capa submucosa alrededor de la cicatriz tras ESD el día antes de la cirugía. En el momento de la cirugía, se visualizaron los ganglios linfáticos ( lymph nodes, LNs) y se realizó la linfadenectomía siguiendo las imágenes de infrarrojo. Ex vivo, todos los LNs se examinaron para detectar la presencia de fluorescencia. Se compararon el número de LNs resecados y el número de LNs afectados por el tumor entre pacientes sometidos a imágenes de infrarrojo y pacientes a los que se les realizó una linfadenectomía convencional sin imágenes intraoperatorias. Resultados: Un total de 290 pacientes fueron sometidos a gastrectomía tras ESD (98 con linfadenectomía por linfografía con ICG y 192 con linfadenectomía convencional). La linfografía con ICG visualizó el drenaje linfático en todos los pacientes, sin complicaciones relacionadas con la inyección de ICG o con las imágenes de infrarrojo. La linfografía con ICG permitió visualizar todas las estaciones ganglionares en las que había LNs metastásicos. La sensibilidad para detectar los LN con metástasis en las estaciones con fluorescencia fue del 100% (9 de 9 estaciones), y el valor predictivo negativo ( negative predictive value, NPV) del 100% (209 de 209 estaciones). Un paciente con metástasis en LN tenía un ganglio metastásico sin fluorescencia en el seno de una estación con fluorescencia. Conclusión: La linfografía con fluorescencia visualiza satisfactoriamente todos los LNs que drenan después de ESD, con una elevada sensibilidad y NPV para detectar metástasis en LN. La linfadenectomía guiada por fluorescencia podría ser una alternativa a la linfadenectomía convencional durante la cirugía adicional después de ESD.